INTENSIFIKASI PAJAK DALAM PENERIMAAN PAJAK PENGHASILAN WAJIB PAJAK BADAN - Ghina, Aliah (2020)
Tax revenue is a source of funds for a country. Researchers want to examine the application of intensification, namely taxpayers, inspection and collection of taxpayers to optimize tax revenue. From this study it can be concluded that the application of tax carried out by (KPP Madya) in the city of Palembang in 2010-2014 has been optimal, as evidenced by the number of taxpayer compliance and tax audits increasing tax revenue exceeding the target 97.21% but not for the results of tax collection which is still less than optimal because the uncollectible rate is still high at 57.01%.